Integrating Conservation for Sustainable Development: Activities of IUCN in Nepal - Joshi, Deependra (Himalayan Review, 2011)
Available with fulltext. Key words: Ecosystem; Bio-diversity; Biotic pressure; Sustainability; Ecology; Mountain environment; Conservation The Himalayan Review Nepal Geographical Society Vol. XXXII 2001 Page: 31-40 Uploaded date: 7 June, 2011